Movies and Learning: Does Watching Movies Help Students Improve Learn English? - Baharum A.; Naim N.F.M.; Ismail R.; Deris F.D.; Noor N.A.M. (Springer Science and Business Media Deutschland GmbH, 2024)
Since English is the most widely used language for communication in the world, mastering English has become essential and important in our lives. Many methods are used to improve the English level, including watching movies. This research aims to study whether watching movies helps students improve their English. This study uses a quantitative method to collect the data through an online questionnaire using Google Forms. The online questionnaire consists of 15 questions with the participation of 250 students from one of the universities in Malaysia, of which each faculty has 25 students for random clustering. The results show that most students usually watch action English movies very often. From the findings, there is no result showing that there is a significant relationship between movie genre preference and English learning. However, it can be concluded that watching movies does help students improve learn English. 2023, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.